Advancing Sustainable Management of Bacterial Spot of Peaches: Insights into Xanthomonas arboricola pv. pruni Pathogenicity and Control Strategies - Nanami Sakata; Yasuhiro Ishiga (Bacteria, 2025)
Peach (Prunus persica) is a fruit crop of significant economic and cultural value, particularly in Japan, where it is cherished for its symbolism of summer and high quality. However, its production is threatened by bacterial spot caused by Xanthomonas arboricola pv. pruni (Xap), a pathogen that also affects other Prunus species such as nectarines, plums, apricots, and almonds. Xap thrives in warm, humid environments and causes symptoms such as water-soaked lesions, necrotic spots, premature defoliation, and fruit blemishes, leading to reduced yield and marketability. Traditional control methods, including copper-based bactericides and antibiotics, are increasingly ineffective due to resistance development and environmental concerns. This review focuses on the biology, epidemiology, and pathogenic mechanisms of Xap, with particular emphasis on its impact on peach production in Japan. We discuss various disease management strategies, such as integrated disease management, biostimulants, cellulose nanofibers, plant defense activators, and biological control agents, alongside novel molecular approaches targeting bacterial virulence factors. By incorporating these innovative and eco-friendly methods with traditional practices, this review offers insights into the potential for sustainable, environmentally friendly solutions to manage bacterial spot and mitigate its impact on peach production.